Identification and quantification of glucose degradation products in heat-sterilized glucose solutions for parenteral use by thin-layer chromatography. - Sarah Leitzen (Public Library of Science (PLoS), 2021)
During heat sterilization of glucose solutions, a variety of glucose degradation products (GDPs) may be formed. GDPs can cause cytotoxic effects after parenteral administration of these solutions. The aim of the current study therefore was to develop a simple and quick high-performance thin-layer chromatography (HPTLC) method by which the major GDPs can be identified and (summarily) quantified in glucose solutions for parenteral administration. All GDPs were derivatized with o-phenylenediamine (OPD). The resulting GDP derivatives (quinoxalines) were applied to an HPTLC plate. After 20 minutes of chamber saturation with the solvent, the HPTLC plate was developed in a mixture of 1,4-dioxane-toluene-glacial acetic acid (49:49:2, v/v/v), treated with thymol-sulfuric acid spray reagent, and heated at 130°C for 10 minutes. Finally, the GDPs were quantified by using a TLC scanner. For validation, the identities of the quinoxaline derivatives were confirmed by liquid chromatography-tandem mass spectrometry (LC-MS/MS). Glyoxal (GO)/methylglyoxal (MGO) and 3-deoxyglucosone (3-DG)/3-deoxygalactosone (3-DGal) could be identified and quantified in pairs, glucosone (2-KDG), 5-hydroxymethylfurfural (5-HMF), and 3,4-dideoxyglucosone-3-ene (3,4-DGE) each individually. For 2-KDG, the linearity of the method was demonstrated in the range of 1-50 μg/mL, for 5-HMF and 3,4-DGE 1-75 μg/mL, for GO/MGO 2-150 μg/mL, and for 3-DG/3-DGal 10-150 μg/mL. All GDPs achieved a limit of detection (LOD) of 2 μg/mL or less and a limit of quantification (LOQ) of 10 μg/mL or less. R2 was 0.982 for 3.4-DGE, 0.997 for 5-HMF, and 0.999 for 2-KDG, 3-DG/3-DGal, and GO/MGO. The intraday precision was between 0.4 and 14.2% and the accuracy, reported as % recovery, between 86.4 and 112.7%. The proposed HPTLC method appears to be an inexpensive, fast, and sufficiently sensitive approach for routine quantitative analysis of GDPs in heat-sterilized glucose solutions.